2023
DOI: 10.1111/peps.12626
|View full text |Cite
|
Sign up to set email alerts
|

When old and new selves collide: Identity conflict and entrepreneurial nostalgia among ex‐entrepreneurs

Jordan D. Nielsen,
J. Jeffrey Gish

Abstract: People undergoing career transitions often bring aspects of old roles into their new work contexts, and this interface can create conflict between lingering aspects of one's work self and the newer aspects of one's work self. Yet, we know little about how this conflict between old and new selves shapes employee outcomes. We examine this issue among ex‐entrepreneurs—individuals who have transitioned from a business owner to a wage employee. Drawing from role identity theory, we develop a model of the consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Perhaps not surprisingly, research on identity conflict has demonstrated the effects it can have on workers’ conceptualizations of one or more of their identities. Identity conflict can lead to struggles adopting the behaviors of a new identity (Vakkayil, 2014), and because one feels that they may not be fulfilling expectations of a valued identity, identity conflict has been theorized to lead to a sense of inauthenticity (Horton et al, 2014; Roberts, 2005) as well as a lack of identity progress (Nielsen & Gish, 2024). Experiencing conflict between one’s identities also can reduce self-esteem and work-related self-efficacy (Barnard, 2019; Settles et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps not surprisingly, research on identity conflict has demonstrated the effects it can have on workers’ conceptualizations of one or more of their identities. Identity conflict can lead to struggles adopting the behaviors of a new identity (Vakkayil, 2014), and because one feels that they may not be fulfilling expectations of a valued identity, identity conflict has been theorized to lead to a sense of inauthenticity (Horton et al, 2014; Roberts, 2005) as well as a lack of identity progress (Nielsen & Gish, 2024). Experiencing conflict between one’s identities also can reduce self-esteem and work-related self-efficacy (Barnard, 2019; Settles et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurial identity is dynamic, and as roles change, so may the nature of one's identity. In our current special issue, Nielsen and Gish (2023) examine the identity conflicts and resulting burnout that ex-entrepreneurs experience when transitioning into the corporate world, especially when they have difficulty letting go of their entrepreneurial past. Further in our special issue, Stevenson et al (2023) show that the salience of one's entrepreneurial identity can be increased through intervention, which can in turn, influence entrepreneurial action.…”
Section: Entrepreneurial Identitymentioning
confidence: 99%
“…Finally, diminished well-being can be an early indicator of subsequent withdrawal behavior. For instance, Nielsen and Gish (2023) link identity conflict between past entrepreneurial identity and current work identity to exentrepreneur's burnout in wage employment. This research helps provide clarity to the higher voluntary turnover of ex-entrepreneurs relative to wage employees (Zhan et al, 2023), suggesting "push" and "pull" back forces into entrepreneurship.…”
Section: Well-being and Wellness Of Entrepreneursmentioning
confidence: 99%
See 1 more Smart Citation